Integrated washland management for flood defence and biodiversity - Morris, Joe; Hess, Tim M.; Gowing, D. J.; Leeds-Harrison, Peter B.; Bannister, N.; Wade, M.; Vivash, R. M. (Cranfield University, 2004)
In the context of growing interest in finding sustainable solutions to flood management in England and Wales, this study set out to determine the extent to which benefits to flood management and biodiversity can be achieved through an integrated approach to the creation and management of ‘washlands’. For the purpose of the study, a washland is defined as “an area of the floodplain that is allowed to flood or is deliberately flooded by a river or stream for flood management purposes, with potential to form a wetland habitat”. Following a questionnaire survey of engineers and conservationists, a review of selected sites, and a workshop of key stakeholders, it was concluded that there is both scope and willingness to exploit potential synergy. It appears, however, that until now most washlands have either been used mainly for flood storage or for wetland habitat, and there has been only a limited attempt to integrate the two objectives. In many respects, the opportunity for integrating biodiversity depends on the ability to maintain wet conditions on the washland beyond the period of the flood event, and this largely depends on the dominant land use. The scope is greatest where the washland is under grass or woodland, and actions can be taken to ‘engineer’ or manage soil wetness regimes which serve biodiversity interests. Such water management plans and related biodiversity targets are best designed into washland management from the outset, rather than as an afterthought, when conflicts of interest are likely to arise. While there is much interest in pursuing an integrated approach, lack of funding for biodiversity on washlands and the relative complexity of preparing the washland case for appraisal appear to constrain washland development. Nevertheless, washlands are perceived by engineers and conservationists alike to offer potentially sustainable solutions to flooding, enabling biodiversity targets to be met within an integrated approach to catchment flood management. Recommendations were made to: • improve, through the use of guidance and training, understanding between engineers and conservationists of how flood management and biodiversity objectives can be simultaneously achieved; • consider the establishment of a biodiversity fund to support the biodiversity components of washland schemes; • develop practical guidance on the formulation of washland management plans that exploit biodiversity potential by managing wetness conditions in washlands beyond the flood-event period; • review how washland creation and management can be integrated and help to deliver the objectives of Biodiversity Action Plans and Catchment Flo